2010
DOI: 10.1074/jbc.m110.127001
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of the CBD1-CBD2 Linker in Slow Dissociation of Ca2+ from the Regulatory Two-domain Tandem of NCX1

Abstract: In NCX proteins CBD1 and CBD2 domains are connected through a short linker (3 or 4 amino acids) forming a regulatory tandem (CBD12). Only three of the six CBD12 Ca , whereas the kinetic and equilibrium properties of three Ca 2؉ sites of CBD12-7Ala and CBD1 ؉ CBD2 are similar. Therefore, the linker-dependent interactions in CBD12 decelerate the Ca 2؉ on/off kinetics at a specific CBD1 site by 50 -80-fold, thereby representing Ca 2؉ "occlusion" at CBD12. Notably, the kinetic and equilibrium properties of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
95
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(104 citation statements)
references
References 50 publications
7
95
1
1
Order By: Relevance
“…Earlier stopped-flow experiments have shown that Ca 2ϩ dissociation from the two high affinity binding sites of CBD12 occurs in two kinetic phases, fast (k f ϭ 4 -7 s Ϫ1 ) and slow (k s ϭ 0.3-0.5 s Ϫ1 ) (17). Because the slow phase of Ca 2ϩ dissociation from CBD12 largely represents the synergistic interactions between the two CBD domains (16,17), we investigated how protons affect Ca 2ϩ off-rates of CBD12.…”
Section: An Investigation Of the Regulation Of Namentioning
confidence: 99%
See 4 more Smart Citations
“…Earlier stopped-flow experiments have shown that Ca 2ϩ dissociation from the two high affinity binding sites of CBD12 occurs in two kinetic phases, fast (k f ϭ 4 -7 s Ϫ1 ) and slow (k s ϭ 0.3-0.5 s Ϫ1 ) (17). Because the slow phase of Ca 2ϩ dissociation from CBD12 largely represents the synergistic interactions between the two CBD domains (16,17), we investigated how protons affect Ca 2ϩ off-rates of CBD12.…”
Section: An Investigation Of the Regulation Of Namentioning
confidence: 99%
“…Stopped-flow Experiments-Quin-2 was used in the stoppedflow experiments to monitor Ca 2ϩ off rates (16,17). In the stopped-flow machine SFM-3 (BioLogic), 150 l (syringe A) of proteins in buffer (100 mM KCl and 10 mM Bistris propane) were mixed with 150 l of buffer plus 200 -600 M Quin-2 (syringe B).…”
Section: Overexpression and Purification Of Cbd1 Cbd2 And Cbd12mentioning
confidence: 99%
See 3 more Smart Citations